From Mars to the Multiverse. (5th December 2017) - Rees, Martin
Abstract : Unmanned spacecraft have visited the other planets of our Solar System (and some of their moons), beaming back pictures of varied and distinctive worlds – but none propitious for life. However, prospects are far more interesting when we extend our gaze to other stars. Most stars are orbited by retinues of planets. Our home Galaxy contains a billion planets like the Earth. Do some of these have biospheres? Moreover, our Galaxy is one of billions visible with a large telescope – all the aftermath of a cosmic 'big bang' 13.8 billion years ago. More astonishing still, 'our' big bang may not have been the only one. The remarkable advances in recent decades are primarily owed to new engineering and technology. Armchair theory alone doesn't get us far.